An Environmental audit for the National Power Corporation's Naga Plant Complex - Matuguina, William R. Jr. (1992)
This research work is an attempt to apply the concepts of environmental auditing to the National Power Corporation's Naga Plant Complex in Cebu. The study presented a review of the present plant environment. Data from the corporation's environmental department and other related studies were major inputs in the review. Review results indicated the need or conduct of an assessment. The audit procedure was patterned from that adapted by the International Chamber og Commerce (ICC) with some modifications to suit its nature of operations. The audit was conducted by the researcher with the assistance from various plants involved. Audit activities lasted for 2 weeks. Initial findings were informally transmitted to concerned personnel. Control measures were considered in the area of noise, particulates and SOx, liquid effluents, hazardous materials (like spent laboratory chemicals, waste oils and sludges, and spent PCB contaminated transformer oils): (1) Noise levels from 3 operator stations can be reduced to occupational levels by using concrete and glass enclosures and with proper ventilations; (2) Improved maintenance, greening to buffer particulate emissions; (3) gaseous SOx, emissions: fuel substitution and increased stack height for CDPP-I; (4) liquid effluents from the water treatment plant are to be reused; (5) the oil-water separator efficiency can be improved by increasing its capacity and use of adsorbents. (6) hazardous substances: the waste oils-sludges are either burned as fuel for CTPP-I or disposed of by land treatment; the waste transformer oils are to be disposed of by scientific landfilling (burned as fuel if PCB levels are insignificant), and the laboratory wastes are disposed of by fixation.
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Environmental auditing -- Philippines -- Cebu; Environmental impact analysis -- Philippines -- Cebu